A new Clathria (Demospongiae, Microcionidae) from Peru occurring on rocky substrates as well as epibiontic on Eucidaris thouarsii sea urchins - Aguirre, LK (2011)
The ESPER Project was funded by the Global Taxonomy Initiative from the Belgian Development Cooperation; the Proyecto EsponjAS was funded by Conselho Nacional de Desenvolvimento Cientifico e Tecnologico (CNPq/PROSUL). K. Aguirre received a grant from Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica (CONCYTEC). The Servicio Nacional de Areas Naturales Protegidas (SERNANP), Agrorural (ex Proabonos) and the Direccion de Hidrografia y Navegacion del Peru are acknowledged for permitting access to Isla Lobos de Afuera and for logistical support.